Serum Creatinine Detection in a Microfluidic Chip Using a Smartphone Camera - Tekin, Hüseyin Cumhur; Karakuzu, B.; Tarim, E.A.; Tekin, H.C. (Chemical and Biological Microsystems Society, 2022)
We present a microfluidic chip platform to detect serum creatinine levels using the enzyme-linked immunosorbent assay (ELISA) principle. In the platform, surface modified microfluidic channel sensitively captured target molecules from the serum sample, and then ELISA protocol was applied inside the channels. Afterward, the blue color formed as a result of the enzymatic reaction was measured via a smartphone camera. The proposed strategy allows the detection of creatinine rapidly in a minute amount of the serum samples without the need for expensive equipment. Thus, chronic kidney disease (CKD) could be monitored easily at point-of-care settings via the proposed creatinine detection strategy. © 2022 MicroTAS 2022 - 26th International Conference on Miniaturized Systems for Chemistry and Life Sciences. All rights reserved.
Chemical and Biological Microsystems Society (CBMS)
26th International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2022 -- 23 October 2022 through 27 October 2022 -- 192912
Keywords: colorimetric analysis; creatinine detection; ELISA; Microfluidics; smartphone testing; Cameras; Colorimetric analysis; Colorimetry; Fluidic devices; Microfluidics; Molecules; Smartphones; Creatinine detection; Enzyme linked immunosorbent assay; Microfluidic-chips; Microfluidics channels; Serum samples; Smart phones; Smart-phone cameras; Smartphone testing; Surface-modified; Target molecule; Creatinine